2023
DOI: 10.1186/s12913-023-09036-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of language barriers on healthcare access and quality among Afaan Oromoo-speaking patients in Addis Ababa, Ethiopia

Abstract: Background Ethiopia is a multilingual and multinational federation with Addis Ababa serving as both the capital city of Oromia regional state and the seat of the Ethiopian federal government. Nevertheless, only Amharic is considered as the working language of the city and federal offices, including hospitals. As a result, Afaan Oromoo-speaking patients may be facing language barriers in the healthcare settings in Addis Ababa. Language barriers have the capacity to affect patients’ experience of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…[28] In accordance with the informants worry regarding making incorrect clinical judgements and assessments, previous research has found that dementia indeed is associated with decreased accuracy of the older patient presenting illness, [29] and that communication barriers pose risks for patients. [13,[15][16][17][18] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [3,10,11,30,31] with one of the found reasons for adverse outcomes being communication barriers. [11] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[28] In accordance with the informants worry regarding making incorrect clinical judgements and assessments, previous research has found that dementia indeed is associated with decreased accuracy of the older patient presenting illness, [29] and that communication barriers pose risks for patients. [13,[15][16][17][18] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [3,10,11,30,31] with one of the found reasons for adverse outcomes being communication barriers. [11] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions.…”
Section: Discussionmentioning
confidence: 99%
“…For healthcare providers, language barriers were found to affect their ability to take patient history, diagnose the patient, provide treatment, and resulted in an increased work burden. [13] In Denmark, a country with fewer Informed consent was obtained from all subjects involved in the study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the current political environment and social issues in the Xinjiang region, such as ethnic relations, religious conflicts, and terrorist attacks, may also have some impact and difficulty on cultural transmission and foreign communication. There is a need to focus on the understanding of historical and political backgrounds in foreign communication and translation, and to strengthen policy support and cultural propaganda so as to promote better dissemination and understanding of minority cultures in Xinjiang [11].…”
Section: Historical and Political Factorsmentioning
confidence: 99%